IMPLEMENTASI METODE BELAJAR KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR IPS KELASVII SMP ADHYAKSA KOTAJAMBI - Tianna Simanjuntak (Universitas Batanghari Jambi, 2017)
Abstract : This classroom Action research is conducted at grade VII of Private Junior High School Adhyaksa which is consist of 28 student. This research begin with the problem faced at grade VII Private Junior High School Adhyaksa, namely low learning achievement on social science, because teacher use conventional method which influence to score of student. According to the previous problem that lack of student participation on social science, and then the process of teaching and learning activity is dominated by teacher or teacher centered, otherwise student do not understand the subject, lack of asking question, only silent, and chatting each other while process of learning. By doing this research is hoped the learning through group discussion method will improve student learning achievement on social science. The objective of this research is to increase student learning achievement on social science on theme natural resources grade IV that the use group discussion method. The kind of this research is Classroom Action Research in two cycles, each cycles consist of four stages namely Planning, Action, Observation, and Reflection. The collecting of data is for namely (1) test, (2) Observation. The result of the research indicatess the successful in increasing student learning achievement on social science through group discussion method thata can be seen by average is 58,57 in first cycle and more increase in second cycle is 84,29. According to preliminary study on student learning achievement is 33,33 % increase to 58,57 % on first cycle and more high in second cycle is 84,29 %. Based on this result is hoped to get information and input for teacher, and all stake holders at Private Junior High School Adhyaksa Jambi.Keywords :Method of Learning, Group Learning and Achievement